Tingkat Pemanfaatan Ikan Tuna (Thunnus albacares) di WPP-NRI 573 yang Didaratkan di Pelabuhan Perikanan Samudera Nizam Zachman Jakarta Utara - Nazmadiah Tri Aryani; Yusrudin Yusrudin; Sumaryam Sumaryam (Manfish: Jurnal Ilmiah Perikanan dan Peternakan, 2025)
Tuna fish (Thunnus albacares) is a fish that has a fairly high economic value and is the dominant catch landed at PPS Nizam Zachman which comes from the WPPNRI 573. Based on the high production results and fishing activities, it is necessary to analyze the utilization level that has been carried out by PPS Nizam Zachman in the WPPNRI 573 for the sustainability of tuna fish (Thunnus albacares). This study aims to determine the CPUE (Catch per Unit Effort), sustainable potential (MSY), utilization level and effort level of tuna fish (Thunnus albacares) landed at PPS Nizam Zachman. This study was conducted on 18 until 30 November 2024. The method used in this study is the Schaefer surplus production method approach. Tuna (Thunnus albacares) were caught using handline fishing gear, purse seines, and tuna longlines. The standard used as the FPI (Fishing Power Index) is the highest CPUE value, namely purse seines. Based on the analysis using the Schaefer model, the intercept value (a) shows 30.864 and the slope (b) is -16.458. The intercept value shows that if there is no fishing effort, the potential for tuna (Thunnus albacares) in WPPNRI 573 available in nature is still 30.864 tons/trip. The MSY catch was 14,469,702 tons, the optimum effort was 938 trips, and the allowable catch was 11,575,762 tons with an average utilization rate of tuna (Thunnus albacares) in WPPNRI 573 landed at PPS Nizam Zachman of 92% with an average effort rate of 106%. This shows that the utilization rate of tuna (Thunnus albacares) in WPPNRI 573 landed at PPS Nizam Zachman is in a dense catch condition.